Fluorine-free non-stick functional coating and preparation method thereof
By using a coating composed of fluorine-free materials, the problem of Teflon non-stick pot coating releasing toxic substances at high temperatures is solved, and the non-stick effect of non-toxic, high temperature resistant and self-lubricating is achieved, and the food safety and daily use needs are met.
Patent Information
- Application Number
- CN202411764200.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
The existing Teflon non-stick pan coating will decompose at high temperatures, releasing toxic substances, causing harm to human health, and the perfluorooctanoic acid that may be used in the production process is harmful to health and lacks a safe alternative.
A non-fluorine non-stick functional coating consisting of non-toxic materials such as polyarylether resin, thermoset melamine, protective colloidal solution, thermally conductive nanocomposite material, far-infrared ceramic powder, wear-resistant filler, etc. is used to grind and refine it through a high-energy ball mill to form a stable suspension state.
It achieves a non-stick effect that is non-toxic, high temperature resistant and self-lubricating, avoids the release of toxic substances, meets the needs of food safety and daily use, and improves the palatability of the rice through far-infrared ceramic powder.
Smart Images

Figure CN119614068A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a fluorine-free non-stick functional coating and a preparation method thereof. Background Art
[0002] Traditional non-stick pan coating, also known as "Teflon", is a general term for fluorinated polymers, including polytetrafluoroethylene, polyperfluoroethylene propylene and various fluorinated copolymers. Because these fluorides have the advantages of high and low temperature resistance, self-lubrication, chemical stability, etc., they are widely used in non-stick cookware, kitchen utensils, waterproof and breathable materials (such as waterproof clothing), engineering parts, automotive parts and high temperature resistant anti-corrosion coatings.
[0003] Teflon is non-toxic under normal conditions, has good lubricity and non-stickiness, low friction coefficient and small surface tension. However, Teflon coating will decompose at high temperatures, releasing toxic substances, such as ammonium perfluorooctanoate, which has potential carcinogenicity and is harmful to human health. In addition, during the production process of Teflon coating, some companies may use perfluorooctanoic acid as a non-stick surfactant. Studies have shown that long-term exposure to perfluorooctanoic acid may have certain effects on human health, such as affecting fertility, growth and development, and remaining in the blood of organisms for a long time.
[0004] At present, there is an urgent need to provide a non-toxic non-stick pan coating with high temperature resistance and self-lubricating properties to replace Teflon. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a fluorine-free non-stick functional coating, which is composed of a primer and a topcoat;
[0006] The primer comprises the following raw materials in parts by weight: 20-22 parts of polyarylether resin; 8 parts of thermosetting melamine; 35-40 parts of protective colloid solution; 2-3 parts of thermal conductive nanocomposite material; 7-10 parts of far-infrared ceramic powder; 8-10 parts of wear-resistant filler; 3-6 parts of coating additive; 8-10 parts of rust-proof pigment; 2 parts of coloring pigment; 20 parts of deionized water;
[0007] The topcoat comprises the following raw materials in parts by weight: 25 parts of polyarylether resin; 8 parts of thermosetting melamine; 30 parts of protective colloid solution; 3-5 parts of thermal conductive nanocomposite material; 7-8 parts of far-infrared ceramic powder; 10 parts of wear-resistant filler; 4 parts of coating additive; 12 parts of coloring pigment; and 20 parts of deionized water.
[0008] Polyarylether resin is a low surface energy resin. Low surface energy resin is a special resin material with extremely low surface energy and outstanding water and oil repellency. This resin material is often used in the fields of anti-sticking, anti-graffiti, as well as anti-fouling coatings for marine ships, bridges, offshore facilities, anti-fouling coatings for fishing gear and other related equipment, and the manufacture of highly hydrophobic coatings for electronic appliances, display screens, etc. In addition, polyarylether resins also have the advantages of being non-toxic, self-extinguishing, and corrosion-resistant, and are used in many fields such as aerospace, automobiles, tableware, and medical equipment.
[0009] Thermally conductive nanocomposites can effectively transfer heat from high-temperature areas to low-temperature areas, helping machines and equipment dissipate heat, prevent overheating damage, and maintain stable and centrally controlled temperature.
[0010] Far infrared ceramic powder is a white powder, which is a mixture of various substances. The main characteristic function of far infrared ceramic powder is that it can radiate more far infrared rays than normal objects (higher infrared radiation rate). The advantage of far infrared ceramic material is that it can convert external energy into heat energy, reduce heat loss, and keep warm for a long time.
[0011] Wear-resistant fillers have extremely low coefficients of friction and can provide excellent lubrication properties in high-load applications, significantly enhancing the wear resistance and lubrication properties of the coating.
[0012] More preferably, the polyarylether-based resin is phthalazine polyether nitrile ketone and / or phthalazine polyether sulfone ketone.
[0013] More preferably, the protective colloid solution is nano zirconium oxide sol and / or nano aluminum oxide sol and / or nano silicon oxide sol and / or polyvinyl alcohol aqueous solution.
[0014] The protective colloid can be any one of commercially available nano zirconium oxide, nano aluminum oxide, and nano silicon oxide sols with a content of 20% to 50%, or a mixed sol of equal mass; the second is to use a commercially available polyvinyl alcohol self-prepared aqueous solution with a content of 1% to 30%; preferably, any one of nano zirconium oxide, aluminum, and silicon, or a mixed sol of equal mass + polyvinyl alcohol aqueous solution, and the best mass ratio is 1:1 to 2.
[0015] More preferably, the anti-rust pigment is flaky active zinc-aluminum powder or phosphate or borate.
[0016] Anti-rust pigments can be selected from phosphates (zinc, aluminum salts), borates (zinc salts), and flaky active zinc-aluminum powder; flaky active zinc-aluminum powder is preferred, and the first two are second.
[0017] Further preferably, the coloring pigment can be any one of carbon black, molybdenum disulfide, titanium dioxide, titanium yellow, iron brown, pearlescent pigment, metallic aluminum pigment or a composite pigment thereof; preferably molybdenum disulfide, the specification requirements are purity ≥ 99%, average particle size 1 to 10 microns, and specific surface area ≥ 10 m2 / g.
[0018] More preferably, the thermally conductive nanocomposite material comprises:
[0019] Graphene; carbon nanotubes; boron nitride whiskers mixture.
[0020] The thermal conductive nanocomposite material is a mixture of graphene, carbon nanotubes and boron nitride whiskers; the graphene has a purity of ≥98% and a number of layers of 2 to 9; the carbon nanotubes have a purity of 95% or more, an outer diameter of 10 to 100 nm, an inner diameter of 5 to 50 nm, a length of 1 to 15 μm, and a specific surface area of more than 60 m2 / g; the boron nitride whiskers have a purity of ≥97%, a whisker diameter of 0.5 to 2.0 μm, a length of 5 to 30 μm, and a specific surface area of more than 10 m2 / g; the mass ratio of graphene, carbon nanotubes and boron nitride whiskers is preferably 1:2:1 (wt).
[0021] Further preferred is the far-infrared ceramic powder, which is a white fine powder mixed with various substances, with the specification requirements: emissivity ≥ 94%, fineness 1000-5000 mesh, and the ability to radiate far-infrared special ceramic powder with a specific wavelength (5-20 μm).
[0022] More preferably, the wear-resistant filler comprises:
[0023] Tungsten carbide and / or silicon nitride and / or solid glass microspheres and / or ceramic microspheres and / or organic silicone spherical microspheres.
[0024] The wear-resistant filler can be any one or a mixture of inorganic tungsten carbide, silicon nitride, solid glass microspheres or ceramic microspheres and organic silicone spherical microspheres, preferably a mixture of solid glass microspheres or ceramic microspheres + silicone spherical microspheres, with the best mass ratio being 4:1 (wt).
[0025] More preferably, the coating additives include:
[0026] Dispersant; defoamer; leveling agent; rheological agent; anti-settling agent; thickener.
[0027] A method for preparing a fluorine-free non-stick functional coating, characterized in that the preparation method specifically comprises the following steps:
[0028] Preparation of primer:
[0029] Step 1: Weigh 20-22 parts of polyarylether resin, 8 parts of thermosetting melamine, 35-40 parts of protective colloid solution, 2-3 parts of thermal conductive nanocomposite material, 7-10 parts of far-infrared ceramic powder, 3-6 parts of coating additive, 8-10 parts of anti-rust pigment, 2 parts of coloring pigment, and 20 parts of deionized water respectively by weight, and mix thoroughly;
[0030] Step 2: Add the mixed materials in the above step 1 into a ball mill for grinding;
[0031] Step 3: Take out the ground mixed material from the grinding equipment in the above step 2, take 8 to 10 parts by weight of wear-resistant filler, add the mixed material and the wear-resistant filler into a disperser, disperse and mix them evenly, and obtain a primer;
[0032] Preparation of topcoat:
[0033] Step 4: weigh 25 parts of polyarylether resin, 8 parts of thermosetting melamine, 30 parts of protective colloid solution, 3-5 parts of thermal conductive nanocomposite material, 7-8 parts of far-infrared ceramic powder, 4 parts of coating additive, 12 parts of coloring pigment, and 20 parts of deionized water, and mix them thoroughly;
[0034] Step 5: Add the mixed materials in the above step 4 into a ball mill for grinding;
[0035] Step 6: Take out the ground mixed material from the grinding equipment in step 5, take 10 parts of wear-resistant filler by weight, add the mixed material and the wear-resistant filler into a disperser, disperse and mix them evenly to obtain a topcoat.
[0036] More preferably, in step 2, the grinding time of the material is more than 1 hour, and the grinding fineness of the material is less than 5 μm, and in step 5, the grinding time of the material is more than 1 hour, and the grinding fineness of the material is less than 5 μm.
[0037] More preferably, the grinding balls in the ball mill are of three sizes: Φ20 mm, Φ15 mm, and Φ10 mm, with a mass ratio of 1:3:6.
[0038] More preferably, the grinding balls in the ball mill are of four sizes: Φ20 mm, Φ15 mm, Φ10 mm, and Φ5 mm, with a mass ratio of 1:2:3:4.
[0039] More preferably, the ratio of the mass of the grinding balls to the mass of the material in the ball mill is 5-6:1.
[0040] The process steps for preparing the above non-stick (pan) coating by the above method are to use various ball mills (rather than sand mills, bead mills, homogenizers) for grinding and refining. As we know from experience, the key technology is the control of grinding fineness. Generally, the smaller the grinding particle fineness, the more stable the system. The best state is that the specific gravity of the particles is less than the specific gravity of water, so that the particles can form a stable suspension state in the water phase system without sedimentation. If you want to grind the material finer, the smaller the diameter of the selected grinding ball is required, but the smaller the grinding ball is, the smaller its impact kinetic energy is. The grinding ball adopts three gradations (Φ20mm, Φ15mm, Φ10mm, mass ratio of 1:3:6) or four gradations (Φ20mm, Φ15mm, Φ10mm, Φ5mm, mass ratio of 1:2:3:4), and the ball-material mass ratio of 5 to 6:1 is the best. The grinding ball can be selected from zirconia balls, alumina balls or stainless steel balls. The advantage of this solution is that the grinding and refining efficiency is high. In about 1 hour, the material fineness can reach less than 15μm. Due to the ball milling without dead angles, the material fineness integral distribution surface is very narrow, within the range of D90 = 1 to 20μm. In addition, the high-energy ball mill is not affected by the viscosity of the material, which is far superior to the sand mill, bead mill and homogenizer.
[0041] The performance test of the coating product of the present invention implements the current national standards such as GB / T 32388-2015, GB / T 32095.1-2015, GB / T32095.2-2015, GB / T 32095.3-2015, etc. Table 1 lists the performance indicators of the fluorine-free non-stick functional coating.
[0042]
[0043]
[0044] The characteristics of the technical product of the present invention can be analyzed by comparing the performance advantages and disadvantages of cookware made of different materials.
[0045] The characteristics of aluminum pots are excellent heat distribution, heat transfer effect is 16 times that of stainless steel pots, and the pot body is lighter. However, aluminum pots are greatly affected by the corrosion of acids, alkalis and salts, are difficult to clean after long-term use, and produce a lot of oil smoke when using cooking oil.
[0046] The characteristic of stainless steel pots is that the heat distribution is uneven, which easily generates hot spots and burns food. Stainless steel pots are heavy, difficult to clean, and easy to smoke when using too much oil.
[0047] The thermal conductivity of an iron pan is better than that of a stainless steel pan, but the heat is uneven, which can easily create hot spots and burn food. The pan is heavy, difficult to clean, prone to rust, and produces a lot of smoke when too much oil is used.
[0048] The characteristics of enamel pots are also uneven heat distribution, easy to burn the bottom of the pot. This kind of pot is not easy to clean, the surface is not easy to bump, easy to break, causing the steel base material to rust.
[0049] The characteristics of ceramic pots are poor thermal conductivity, uneven heat distribution, low thermal energy utilization, and energy consumption. They are also easy to get stuck on the bottom, difficult to clean, and easily damaged on the surface.
[0050] Teflon non-stick pans overcome all the shortcomings of traditional pans. They are easy to clean and do not stick to the bottom of the pan when frying, stir-frying or cooking. However, their shortcomings are also obvious. When heated, the coating becomes soft and easily scratched. When overheated, it will coke and release toxic fumes. The thermal conductivity is poor and the heating is uneven. These shortcomings are insurmountable. In addition, Teflon products are toxic as mentioned above.
[0051]
[0052]
[0053] The coating product of the present invention overcomes the various disadvantages of the above-mentioned kitchen utensils and makes up for the inherent deficiencies.
[0054] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0055] The coating is made of non-toxic materials such as polyarylether resin. The coating has the original characteristics of Teflon non-stick pan, which is easy to clean and does not stick to the bottom of the pan when frying, stir-frying or cooking. In addition, the coating is non-toxic, which can meet the needs of daily use and food safety. Far-infrared ceramic powder is excited to release far-infrared electromagnetic waves when heated. The small molecular clusters of water produced penetrate into the cell membrane of rice grains, making the starch structure inside the rice grains absorb water, become fluffy and flexible, and improve the palatability of rice. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Attached Figure 1 This is the particle size distribution detection diagram of the coating nanomaterial;
[0057] Attached Figure 2 This is an electron microscope test picture of the material dispersion state;
[0058] Attached Figure 3 This is an electron microscope test picture of the material dispersion state;
[0059] Attached Figure 4 This is an electron microscope test picture of the material dispersion state;
[0060] Attached Figure 5 This is an electron microscope image of the mixed material before ball milling. DETAILED DESCRIPTION
[0061] Attached Figure 1 This is a test chart of the particle size distribution of the coating nanomaterial, which shows that the nanoparticles of the processed material dispersed by mechanical ball milling have entered the nanoscale and achieved the processing requirements. Figure 2 Comparison pictures of the dispersion state of materials before and after ball milling under electron microscope. Figure 2 , Attachment Figure 3 And attached Figure 4 The pictures are scattered and taken from different angles. Figure 5 This is an electron microscope picture of the mixed material before ball milling. From the comparison and analysis of the electron microscope pictures, the dispersion state of the materials after ball milling is relatively uniform, and the nanoparticles are all in the nanometer scale (less than 100nm), while the materials before ball milling are in a state of agglomeration and chaos. Figure 1 -Attached Figure 5 The present invention is further described in detail.
[0062] In the following examples, all product names with or without model numbers are commercially available products that can be purchased in the chemical market, and the manufacturers and suppliers are not listed. For uncommon raw material products, the manufacturer or supplier name is indicated.
[0063] Example 1
[0064] Preparation of two-coat fluorine-free non-stick (pan) coating:
[0065] 1. Preparation of primer: by mass, take 12 parts of PPENK solid resin powder (molecular weight ≥ 60000, average particle size ≤ 200μm), 10 parts of PPESK solid resin powder (molecular weight ≥ 60000, average particle size ≤ 200μm, supplied by Chengdu Tianshun Poly), 8 parts of MF thermosetting melamine toughened resin powder, 5 parts of PVA17-88 polyvinyl alcohol resin powder, 35 parts of ZG-50 neutral nano silica sol, 8 parts of ZP-108 zinc aluminum phosphate antirust pigment, 2 parts of MA-100 pigment carbon black, 2 parts of thermal conductive nano composite material (self-prepared), 7 parts of YT-F001 far-infrared ceramic powder. 1 part, AG-221 nano material wetting agent 1 part, KYC-913 nano material dispersant 2 parts, X-106 water-based antifoaming and defoaming agent 0.5 parts, BYK-349 water-based polyether leveling agent 0.5 parts, 1500X water-based magnesium aluminum silicate thickener 1 part, A200 fumed silica 1 part; adjust the above materials to a suitable viscosity for grinding with 20 parts of deionized water, and then place them in a high-energy ball mill for ball milling for 1 hour, the coating fineness can reach less than 5μm, and then add 8 parts of solid glass beads after discharging, totaling 103 parts (including 3 parts of production loss), and disperse and mix evenly at high speed to obtain a polymer alloy fluorine-free non-stick (pan) primer.
[0066] 2. Preparation of topcoat: by mass, take 25 parts of PPESK solid powder resin (molecular weight ≥ 60000, average particle size ≤ 200μm), 8 parts of MF thermosetting melamine toughening resin powder, 5 parts of PVA17-88 polyvinyl alcohol resin powder, 25 parts of ZG-50 neutral nano silica sol, 2 parts of AG-221 nano material wetting agent, 2 parts of KYC-913 nano material dispersant, 2 parts of MA-100 pigment carbon black, and 2 parts of MoS 2 -002 molybdenum disulfide 10 parts, thermal conductive nano composite material 3 parts, YT-F001 far-infrared ceramic powder 7 parts, CY-L30W α-phase nano alumina 1 part, X-106 water-based antifoam defoamer 0.5 parts, BYK-349 water-based polyether leveling agent 0.5 parts, 1500X water-based magnesium aluminum silicate thickener 1 part, A200 fumed silica 1 part, the above materials are adjusted to a suitable viscosity for grinding with 20 parts of deionized water, and then placed in a high-energy ball mill for 1 hour. The coating fineness can reach less than 5μm. After discharging, add 2 parts of SA-1930A silicone spherical micropowder and 8 parts of solid glass microbeads, a total of 103 parts (including 3 parts of production loss), and disperse and mix evenly at high speed to obtain a polymer alloy fluorine-free non-stick (pan) topcoat.
[0067] The functions of the materials in the above coating formula components are as follows:
[0068] The PPENK and PPESK described in the formula are poly(phenylene ether sulfone (nitrile) ketone) of phthalazine, which are insoluble resin powders in the present formula system, and have a melting point of 340° C. Therefore, the present invention sets the film-forming sintering temperature at 350° C. in the technical indicators;
[0069] The thermosetting melamine (MF) is used as an insoluble resin toughening agent in the present formulation system, and plays a role in fluxing and toughening the coating;
[0070] The polyvinyl alcohol resin powder can be dissolved in water to form a colloid at room temperature, acting as a binder in the system, and decomposes into CO at a high temperature of 300°C. 2 The gas is released from the system, but it remains in the system as a non-carbonized substance and affects the coating quality, so it is called a protective colloid;
[0071] The nano-silicon dioxide (aluminum / zirconium) sol is a type of inorganic nano-film-forming material, which plays a hybrid enhancement role on the organic film-forming material;
[0072] The wetting agent, dispersant, defoamer and leveling agent mentioned above are all functional liquid coating additives, and their functions are consistent with their names, so they will not be described in detail;
[0073] The magnesium aluminum silicate and fumed silica are powder coating additives that play a role in thickening, anti-settling and anti-sagging in water-based coating systems;
[0074] The zinc aluminum phosphate (including the flaky zinc powder in the subsequent embodiments) is used as a functional pigment for primer in the coating to prevent rust or provide cathode protection.
[0075] The thermal conductive nanocomposite material and far-infrared ceramic powder have been described above and will not be described in detail.
[0076] The pigment carbon black (including the flash aluminum silver paste, pearl powder, etc. in the subsequent embodiments) and molybdenum disulfide (coloring self-lubricant) are all coloring pigments in the coating, which give the coating color and flash or magic color effect;
[0077] The silicone spherical micropowder is used as a lubricating and non-sticking agent to replace the perfluorooctanoic acid (PFOA) lubricant banned in Teflon in the present invention;
[0078] The solid glass microbeads have a particle size range of 4 to 5 μm and play a role in anti-scratch and wear resistance in the coating.
[0079] The above description of the effects of the materials is the same in the following embodiments, so it will not be repeated here.
[0080] Example 2
[0081] Preparation of two-coat fluorine-free non-stick (pan) coating:
[0082] 1. Preparation of primer: by mass, take 22 parts of PPENK solid resin powder (SK-2, molecular weight ≥ 60000, average particle size ≤ 200μm, manufacturer: Chengdu Tianshun Poly New Materials), 8 parts of TPU thermosetting melamine toughened resin powder, 3 parts of KYC-913 nano material dispersant, 10 parts of PVA17-88 polyvinyl alcohol resin powder, 30 parts of ZG-40 alkaline nano silica sol, 2 parts of nano thermal conductive composite functional material, 8 parts of ZP-20 zinc phosphate anti-rust pigment, 2 parts of MA-100 pigment carbon black, and 10 parts of YT- 7 parts of F001 far-infrared ceramic powder, 0.5 parts of BYK-349 water-based polyether leveling agent, 0.5 parts of X-106 water-based antifoaming and defoaming agent, 1 part of 1500X water-based aluminum magnesium silicate thickener, and 1 part of A200 fumed silica; adjust the above materials to a suitable viscosity for grinding with 20 parts of deionized water, and then place them in a high-energy ball mill for ball milling for 1 hour. The paint fineness can reach less than 5μm. After discharging, add 8 parts of solid glass beads, totaling 103 parts (including 3 parts of production loss), and disperse and mix evenly at high speed to obtain a polymer alloy fluorine-free non-stick (pan) primer.
[0083] 2. Preparation of topcoat: by mass, take 25 parts of PPESK solid powder resin (molecular weight ≥ 60000, average particle size ≤ 200μm), 8 parts of TPU thermosetting melamine toughened resin powder, 5 parts of PVA17-88 polyvinyl alcohol resin powder, 25 parts of ZG-40 alkaline nano silica sol, 1 part of AG-221 nano material wetting agent, 2 parts of KYC-913 nano material dispersant, 2 parts of MA-100 pigment carbon black, and 2 parts of MoS 2 -002 molybdenum disulfide 10 parts, nano thermal conductive composite functional material 3 parts, YT-F001 far-infrared ceramic powder 8 parts, CY-L30W α-phase nano alumina 1 part, X-106 water-based antifoam defoamer 0.5 parts, BYK-349 water-based polyether leveling agent 0.5 parts, 1500X water-based magnesium aluminum silicate thickener 1 part, A200 fumed silica 1 part, adjust the above materials to a suitable viscosity for grinding with 20 parts of deionized water, and then place them in a high-energy ball mill for 1 hour. The coating fineness can reach less than 5μm. After discharging, add 2 parts of SA-98 silicone powder and silicone micropowder and 8 parts of solid glass beads, totaling 103 parts (including 3 parts of production loss), and disperse and mix evenly at high speed to obtain a polymer alloy fluorine-free non-stick (pan) topcoat.
[0084] Example 3
[0085] Preparation of two-coat fluorine-free non-stick (pan) coating:
[0086] 1. Preparation of primer: by mass, take 20 parts of PPESK solid resin powder (SK-2, molecular weight ≥ 60000, average particle size ≤ 200μm, manufacturer: Chengdu Tianshun Poly New Materials), 8 parts of TPU thermosetting melamine toughened resin powder, 5 parts of PVA17-88 polyvinyl alcohol resin powder, 30 parts of SS-LA25W nano alumina sol, 10 parts of 4-5μm flaky zinc powder, 2 parts of MA-100 pigment carbon black, 3 parts of thermal conductive nanocomposite material, 10 parts of YT-F001 far-infrared ceramic powder, KYC-913 2 parts of nano material dispersant, 0.5 parts of X-106 water-based antifoaming and defoaming agent, 0.5 parts of BYK-349 water-based polyether leveling agent, 1 part of 1500X water-based magnesium aluminum silicate thickener, 1 part of A200 fumed silica; adjust the above materials to a suitable viscosity for grinding with 20 parts of deionized water, and then place them in a high-energy ball mill for ball milling for 1 hour, the coating fineness can reach less than 5μm, and then add 10 parts of solid glass beads after discharging, totaling 103 parts (including 3 parts of production loss), and disperse and mix evenly at high speed to obtain a polymer alloy fluorine-free non-stick (pan) primer.
[0087] 2. Preparation of topcoat: by mass, take 25 parts of PPESK solid powder resin (molecular weight ≥ 60000, average particle size ≤ 200μm), 8 parts of TPU thermosetting melamine toughened resin powder, 5 parts of PVA17-88 polyvinyl alcohol resin powder, 25 parts of SS-LA25W nano alumina sol, 2 parts of KYC-913 nano material dispersant, 2 parts of MA-100 pigment carbon black, and 2 parts of MoS 2 -002 molybdenum disulfide 10 parts, thermal conductive nano composite material 5 parts, YT-F001 far-infrared ceramic powder 7 parts, CY-L30W α-phase nano alumina 1 part, X-106 water-based antifoam defoamer 0.5 parts, BYK-349 water-based polyether leveling agent 0.5 parts, 1500X water-based aluminum magnesium silicate thickener 1 part, A200 fumed silica 1 part, the above materials are adjusted to a suitable viscosity for grinding with 20 parts of deionized water, and then placed in a high-energy ball mill for 1 hour. The coating fineness can reach less than 5μm. After discharging, TY-360 polytetrasilyl sesquisilone microspheres 2 parts and solid glass microspheres 8 parts are added, totaling 103 parts (including 3 parts of production loss), and high-speed dispersion and mixing are uniform, which is a polymer alloy fluorine-free non-stick (pan) topcoat.
[0088]
[0089] The coatings and coating processes of Examples 1 to 3 adopt a "wet-on-wet" process, that is, after spraying the primer, drying at 120°C, spraying the topcoat, and then gradually raising the temperature from 60°C to 350°C / 30min for high-temperature plasticization.
[0090] The main physical and chemical properties test results of the coating products of Examples 1 to 3 are shown in Table 4.
[0091]
[0092]
[0093] Comparative Example 1
[0094] GJ-9546A / 9171B Teflon non-stick pan coating (two-component), divided into primer and topcoat (commercially available). Prepare the sample: Shot blast or sandblast the surface of the test plate (roughness requirement reaches I SO Rz = 40μm), and heat it, spray a primer, and dry it at 120℃; spray a topcoat, if filled with molybdenum disulfide filler, temperature treatment should be carried out at 250℃; sintering temperature is controlled at 375~380℃ / 20~30min; cool down, and the temperature should not be too fast.
[0095] Comparative Example 2
[0096] GJ-8110 (B / A) nano ceramic non-stick pan coating (two-component), divided into primer and topcoat (commercially available). When using, mix the A / B components in proportion, put them into a sealed can and roll them for 2 to 3 hours, and then spray them after cooling and filtering.
[0097] When the substrate is aluminum, iron, stainless steel, pottery, etc., the pre-treatment of different substrates is different, but sandblasting must be performed. The construction process is as follows:
[0098] 1. Degreasing / sandblasting (degreasing uses surfactant cleaning, and shot blasting / sand blasting uses 40-80 mesh steel shot, corundum or brown corundum);
[0099] 2. Spray primer (dry film thickness should be kept between 15 and 20 μm);
[0100] 3. Spray the surface oil (it is best to spray the surface oil when the base oil is not completely dry, and the dry film thickness should be kept between 10 and 15 μm);
[0101] 4. Curing at 280℃ / 10min (the temperature should not be raised too quickly, and it should be kept from room temperature to 280℃ for more than 15min).
[0102] The test results of comparative examples 1 and 2 and the coating and coating performance of the present invention are shown in Tables 5 and 6.
[0103]
[0104]
[0105] From the comparative test results in Table 5, it can be seen that the coating product of the present invention is not inferior to Teflon non-stick coating in performance, and some indicators (such as single-layer coating thickness, adhesion, hardness, and wear resistance) are even better than Teflon coating, and can completely replace Teflon coating.
[0106]
[0107] From the comparative test results in Table 6, it can be seen that the use and operation of nano-ceramic coatings are relatively cumbersome, the process is relatively complicated, and the spray dry film cannot be too thick (10-15 μm), otherwise the coating is easily cracked and broken due to the influence of drying shrinkage stress, which is the fatal weakness of ceramic coatings; in terms of coating solid content, non-stickiness and other indicators, the coating and coating performance of the present invention are also better than nano-ceramic coatings; the hardness of the nano-ceramic coating is higher than the coating index of the present invention, which just highlights the disadvantages of the nano-coating that it is hard and brittle. The bumps and collisions of the coating equipment during use can easily lead to the fragmentation and damage of the ceramic coating.
[0108]
[0109] Table 7 and Appendix Figure 1Combined with the laser particle size analysis test report of the coating of Example 1, it is shown that the nanoparticles of the processed material dispersed by mechanical ball milling have entered the nanometer scale, achieving the processing requirements.
[0110] This specific embodiment is merely an explanation of the invention and is not a limitation of the invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as they are within the scope of protection of the invention, they are protected by patent law.
Claims
1. A fluorine-free non-stick functional coating, characterized in that: It consists of a primer and a topcoat; The primer comprises the following raw materials in parts by weight: 20-22 parts of polyarylether resin; 8 parts of thermosetting melamine; 35-40 parts of protective colloid solution; 2-3 parts of thermal conductive nanocomposite materials; 7-10 parts of far-infrared ceramic powder; 8-10 parts of wear-resistant fillers; 3-6 parts of coating additives; 8-10 parts of rust-proof pigments; 2 parts of coloring pigments; 20 parts of deionized water; The topcoat comprises the following raw materials in parts by weight: 25 parts of polyarylether resin; 8 parts of thermosetting melamine; 30 parts of protective colloid solution; 3-5 parts of thermal conductive nanocomposite material; 7-8 parts of far-infrared ceramic powder; 10 parts of wear-resistant filler; 4 parts of coating additives; 12 parts of coloring pigments; 20 parts of deionized water.
2. The fluorine-free non-stick functional coating according to claim 1, characterized in that: The polyarylether resin is phthalazine polyether nitrile ketone and / or phthalazine polyether sulfone ketone.
3. The fluorine-free non-stick functional coating according to claim 1, characterized in that: The protective colloid solution is nano zirconium oxide sol and / or nano aluminum oxide sol and / or nano silicon oxide sol and / or polyvinyl alcohol aqueous solution.
4. The fluorine-free non-stick functional coating according to claim 2, characterized in that: The anti-rust pigment is flaky active zinc-aluminum powder or phosphate or borate.
5. The fluorine-free non-stick functional coating according to claim 1, characterized in that: The thermally conductive nanocomposite material comprises: Graphene; carbon nanotubes; boron nitride whiskers mixture.
6. The fluorine-free non-stick functional coating according to claim 1, characterized in that: The wear-resistant filler comprises: Tungsten carbide and / or silicon nitride and / or solid glass microspheres and / or ceramic microspheres and / or organic silicone spherical microspheres.
7. The fluorine-free non-stick functional coating according to claim 1, characterized in that: The coating additives include: Dispersant; defoamer; leveling agent; rheological agent; anti-settling agent; thickener.
8. The method for preparing a fluorine-free non-stick functional coating according to any one of claims 1 to 7, characterized in that: The preparation method specifically comprises the following steps: Preparation of primer: Step 1: Weigh 20-22 parts of polyarylether resin, 8 parts of thermosetting melamine, 35-40 parts of protective colloid solution, 2-3 parts of thermal conductive nanocomposite material, 7-10 parts of far-infrared ceramic powder, 3-6 parts of coating additive, 8-10 parts of anti-rust pigment, 2 parts of coloring pigment, and 20 parts of deionized water respectively by weight, and mix thoroughly; Step 2: Add the mixed materials in the above step 1 into a ball mill for grinding; Step 3: Take out the ground mixed material from the grinding equipment in the above step 2, take 8 to 10 parts by weight of wear-resistant filler, add the mixed material and the wear-resistant filler into a disperser, disperse and mix them evenly, and obtain a primer; Preparation of topcoat: Step 4: weigh 25 parts of polyarylether resin, 8 parts of thermosetting melamine, 30 parts of protective colloid solution, 3-5 parts of thermal conductive nanocomposite material, 7-8 parts of far-infrared ceramic powder, 4 parts of coating additive, 12 parts of coloring pigment, and 20 parts of deionized water, and mix them thoroughly; Step 5: Add the mixed materials in the above step 4 into a ball mill and grind them; Step 6: Take out the ground mixed material from the grinding equipment in step 5, take 10 parts of wear-resistant filler by weight, add the mixed material and the wear-resistant filler into a disperser, disperse and mix them evenly to obtain a topcoat.
9. The method for preparing the fluorine-free non-stick functional coating according to claim 8, characterized in that: The grinding time of the material in the step 2 is more than 1 hour, and the grinding fineness of the material is less than 5 μm. The grinding time of the material in the step 5 is more than 1 hour, and the grinding fineness of the material is less than 5 μm.
10. The method for preparing the fluorine-free non-stick functional coating according to claim 8, characterized in that: The grinding balls in the ball mill equipment are of three grades: Φ20mm, Φ15mm, and Φ10mm, with a mass ratio of 1:3:
6.
11. The method for preparing the fluorine-free non-stick functional coating according to claim 8, characterized in that: The grinding balls in the ball mill equipment adopt four grades: Φ20mm, Φ15mm, Φ10mm, and Φ5mm, and the mass ratio is 1:2:3:
4.
12. The method for preparing the fluorine-free non-stick functional coating according to claim 8, characterized in that: The ratio of the mass of the grinding balls to the mass of the materials in the ball mill is 5-6:1.